2020
DOI: 10.21079/11681/35196
|View full text |Cite
|
Sign up to set email alerts
|

Measuring climate and extreme weather vulnerability to inform resilience, report 1 : a pilot study for North Atlantic medium- and high-use maritime freight

Abstract: This research identified vulnerability indicators from open-data sources that represent the three components of vulnerability, as outlined by the Intergovernmental Panel on Climate Change: exposure, sensitivity, and adaptive capacity. With input from experts knowledgeable in port operations, planning, policy, and data, researchers refined a set of highlevel vulnerability indicators to answer the following key questions: (1) how sufficient is the current state of U.S. seaport sector data for developing expert-s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2
1

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 52 publications
0
5
0
Order By: Relevance
“…This appendix explains that a port's level of vulnerability, in terms of adaptive capacity, is strongly tied to its decision-makers' understanding of the risks and potential impacts and acting upon that knowledge. This is of interest to this study, as the adaptive capacity element of the vulnerability component had the lowest ranking during the expert evaluation process (McIntosh et al 2019). As mentioned earlier, study respondents most often explained vulnerability in terms of a port's exposure and sensitivity.…”
Section: Discussionmentioning
confidence: 82%
See 3 more Smart Citations
“…This appendix explains that a port's level of vulnerability, in terms of adaptive capacity, is strongly tied to its decision-makers' understanding of the risks and potential impacts and acting upon that knowledge. This is of interest to this study, as the adaptive capacity element of the vulnerability component had the lowest ranking during the expert evaluation process (McIntosh et al 2019). As mentioned earlier, study respondents most often explained vulnerability in terms of a port's exposure and sensitivity.…”
Section: Discussionmentioning
confidence: 82%
“…This report captures the first of a twopart study. In the first part of the study (McIntosh et al [2019], Measuring Climate and Extreme Weather Vulnerability to Inform Resilience: Report 1: Pilot Study for North Atlantic Medium-and High-Use Maritime Freight Nodes), experts ranked higher the use of exposure and sensitivity indicators as measures of ports vulnerability. This report is a summary of the second part of the study.…”
Section: Executive Summarymentioning
confidence: 99%
See 2 more Smart Citations
“…The motivation behind this study began with the need to better understand the "adaptive capacity" to climate and extreme weather events for medium-and high-use seaports in North Atlantic. Our earlier study identified "seaport vulnerability indicators" in order to inform metrics for seaport resilience (McIntosh et al, 2019). In that study, vulnerability consists of three key components: exposure, sensitivity, and adaptive capacity.…”
Section: Discussionmentioning
confidence: 99%